Discussion issues in regulatory consequences of surgical help delivery in accordance to principles of a new medical reform - P. F. Muzychenko; А. М. Bilyakov; N. М. Ergard (Клінічна хірургія, 2018)
Objective. To discuss an acute issues of possible loyal consequences of the surgical help giving in accordance to positions of a new medical reform.